Development of a Character Education Model Based on Aswaja An-Nahdliyah Values and Local Wisdom in Islamic Higher Education - Zainudin, Agus; Supandi, Ach. Faqih; Masruroh, A`imatul (Pascasarjana Universitas KH. Abdul Chalim, 2025)
Islamic higher education institutions bear a significant responsibility in shaping students’ character to align with noble values and Aswaja An-Nahdliyah principles. One of the efforts undertaken is to develop a learning model that integrates local wisdom with Aswaja An-Nahdliyah values. This study aims to produce a well-developed product, specifically a character education model based on Aswaja An-Nahdliyah and local wisdom that is effective in building students’ character in Islamic higher education. This learning model is expected to assist lecturers in nurturing students’ character under Aswaja An-Nahdliyah's values and local wisdom, thereby shaping students into future generations with noble character and national insight. The research method used is qualitative descriptive with a case study approach. Data collection techniques include observation, interviews, and documentation, while data analysis methods involve data reduction, data display, and data verification. The results of this study indicate that the learning model based on local wisdom and Aswaja An-Nahdliyah values, developed, internalized, and integrated into the Aswaja An-Nahdliyah Character course through teaching, academic studies, and academic culture, has provided understanding and reinforcement of Aswaja An-Nahdliyah creed among students.